Genetic analysis of fiber-dimension traits and combined selection for simultaneous improvement of growth and stiffness in lodgepole pine (Pinus contorta) - Hayatgheibi, Haleh; Fries, Anders; Kroon, Johan; Wu, Harry (NRC Research Press (a division of Canadian Science Publishing), 2019)
Quantitative genetic variation of fiber-dimension traits and their relationship with diameter at breast height (DBH) and solid-wood traits (i.e. density and modulus of elasticity (MOE)) was investigated in lodgepole pine (Pinus contorta Dougl. ex Loud. var. latifolia Engelm.). A total of 823 increment cores were sampled from 207 half-sib families at two independent progeny trials, aged 34-35 year, located in northern Sweden. High-resolution pith-to-bark profiles were obtained for radial fiber width (RFW), tangential fiber width (TFW), fiber wall thickness (FWT), and fiber coarseness (FC) using SilviScan. Heritabilities ranged from 0.29 to 0.74 and inheritance increased with cambial maturity. Estimated age-age genetic correlations indicate that early selection between ages 5 and 8 years is highly efficient. Our results indicate that selection for a 1% increase in DBH or MOE incurs a negligible effect on fiber-dimension traits and maximum genetic gains are reached when DBH and MOE are considered jointly. Moreover, simultaneous improvement of growth and stiffness is achievable when a selection index with 7 to 10 economical weights for MOE relative to 1 for DBH is incorporated. However, the unfavorable relationship between solid-wood and pulp and paper-related traits suggests that breeding strategies must be implemented to improve wood quality of lodgepole pine for multiple uses. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.